Episodic ataxia type 1 without episodic ataxia: the diagnostic utility of nerve excitability studies in individuals with KCNA1 mutations. (5th August 2013) - Tan, S Veronica; Wraige, Elizabeth; Lascelles, Karine; Bostock, Hugh
Abstract : Episodic ataxia type 1 (EA1) is caused by mutations in the KCNA1 gene encoding the fast potassium channel Kv1.1 and is characterized clinically by brief episodes of ataxia and continuous and spontaneous motor unit activity. Atypical presentations, in which the predominant manifestation is related to the peripheral nervous system, may lead to the diagnosis being missed or delayed, with the potential risk of individuals receiving inappropriate or unnecessary investigations and treatment. We present a case of a 15‐year‐old female with EA1 who had never had episodes of ataxia, and whose hand movements were initially thought to represent a tremor. Genetic screening for KCNA1 mutations was precipitated by the results of the nerve excitability studies (TROND protocol), which showed changes typical of reduced fast potassium channel conductance. This case highlights the utility of nerve excitability studies in identifying individuals with KCNA1 mutations.